2003
DOI: 10.1097/00001813-200311000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine monotherapy and in combination with immunotherapy in the treatment of metastatic renal cell carcinoma

Abstract: This prospective trial aimed to evaluate the therapeutic effects and systemic toxicities of capecitabine monotherapy and capecitabine treatment combined with biological response modifiers in patients with metastatic renal cell carcinoma. Fifty-four patients suffering from metastatic renal cell carcinoma progressing under first-, second- or third-line treatment entered the trial. Capecitabine was given orally at a dose of 2500 mg/m2 daily divided into two doses for 14 days, followed by a 7-day rest in the monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…in the subgroup analysis (CB 91.7 vs. 66.7%), highlighting the importance of the timing of chemotherapy in treatment planning [19]. Considering the response rate (RR) of 15-20% reached by the standard first-line immunotherapy based on IL-2 or IFN-a [80,81], capecitabine treatment, combined or not with immunotherapy, led to a huge overall RR to in this study, 19.2%, (including both PR, defined as 50% or greater reduction of the tumor mass, and MR, defined as 25-50% decreased tumor size, according to the World Health Organization criteria) [82].…”
Section: Review Monochemotherapymentioning
confidence: 95%
“…in the subgroup analysis (CB 91.7 vs. 66.7%), highlighting the importance of the timing of chemotherapy in treatment planning [19]. Considering the response rate (RR) of 15-20% reached by the standard first-line immunotherapy based on IL-2 or IFN-a [80,81], capecitabine treatment, combined or not with immunotherapy, led to a huge overall RR to in this study, 19.2%, (including both PR, defined as 50% or greater reduction of the tumor mass, and MR, defined as 25-50% decreased tumor size, according to the World Health Organization criteria) [82].…”
Section: Review Monochemotherapymentioning
confidence: 95%
“…The authors reckon that this combination regimen has at least modest activity in patients with metastatic RCC. Wenzel et al (2003) used capecitabine, an orally administered fluoropyrimidine carbamate that is activated by a three-step enzymatic conversion to 5-FU, to treat several patient cohorts with metastatic RCC refractory to immunotherapy in second-and third-line settings. In a subgroup of 24 patients who received second-line capecitabine monotherapy at 2500 mg/m 2 daily divided into two doses for 14 days, followed by a 7-day rest, the authors observed a clinical benefit in 22 patients (92%).…”
Section: Chemotherapymentioning
confidence: 99%
“…Clinical trials of 5-fluorouracil (5FU) and its oral analog, capecitabine, have shown modest activity for these agents in RCC 14,15. Other studies have similarly shown modest activity of gemcitabine in RCC 16,17.…”
Section: Introductionmentioning
confidence: 99%